2-Methyl-3,5,6-triphenyl-2,3-dihydropyrazine - Anuradha, N. (International Union of Crystallography, 2009)
In the title molecule, C(23)H(20)N(2), the heterocyclic ring adopts a screw-boat conformation, with all substituents equatorial. The phenyl ring at position 3 makes dihedral angles of 78.12 (15) and 72.67 (15)°, respectively, with the phenyl rings at positions 5 and 6; the dihedral angle between the phenyl rings at positions 5 and 6 is 67.32 (14)°. A C—H⋯π interaction is present in the crystal structure.